ҒАРБ АДАБИЙ ТАФАККУРИНИНГ ЎЗБЕК АДАБИЁТИГА ТАЪСИРИ - Алланазарова, Ф.К. (SCIENCE and SOCIETY, 2024)
The article states that in each work of the writer, a symbol can be created in the world of fantasy, or it can be a reality of an already existing life. In the stories of N.Eshonqul, the metaphor-symbol acquires universality and is focused on exposing the evils that negatively affect the internal balance of the society. Whether it is about love or the life of a society, it appears in the summarization of the life of a human being who is going through dreams and back-and-forth. Mythopoetic elements are very different from the imagination of Westerners , we witness that in some of his stories he spoke about the fate of nameless heroes, and such bitter truths about the lives of nameless heroes were embodied in the author's imagination. In it, the writer evokes the imagination as a storyteller, a narrator, and a direct participant in reality at the same time. Here, the writer evokes the imagination as a storyteller, a narrator, and a direct participant in reality at the same time.
Keywords: story; legend; oppression; violence; symbol; harmony; truth; character; means; body; plot; interpretation; presence